Perilaku Pencarian Pengobatan terhadap Penyakit Tidak Menular pada Masyarakat - Arkham Sukmana Aji; Arif Widodo (Journal of Telenursing (JOTING), 2023)
This study aims to determine community behavior in seeking treatment for PTM and the level of public knowledge about seeking therapy for PTM. The method used in this research is descriptive qualitative. The results obtained from this study are that most people seek treatment for PTM at a doctor's clinic, and the majority of community education are high school graduates. This study concludes that informants trust the doctor's clinic more, and there is a difference between the knowledge of informants who attend school and those who do not. Keywords: Medicine, Non-communicable Diseases, Behavior